KETERLAMBATAN MAHASISWA DALAM PENYELESAIAN TUGAS AKHIR DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Beni Affandi; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Students delay in completing their final at the Faculty of Social and Political Sciences, Riau University. This research was conducted in the Faculty of Social and Political Sciences, University of Riau. As the purpose of this study was held to find out what is the causes that influence students late in completing their final project. In this research, the theory used is Habitus Pierre Bourdieu's theory or habit. The research method used is the phenomenological qualitative method, in determining the informants using purposive sampling technique, that choose by determining the target informants who will be selected with predetermined criteria. Data collection techniques by conducting observations, interviews and documentation from 7 informants who meet the criteria and agree to be interviewed. The results of the research obtained are, the habit of students being late in completing their final projects tends to often participate in organizations within the campus and outside the campus, often cheating occurs to absences by leaving absences, the study habits of informants are generally not very diligent in studying, and mostly from the answer, the informants stated that they often postpones assignments given by the lecturer. From the results of interviews with informants, many states that apart from lectures, the informants also worked as freelance to cover their costs while studying abroad. The causes and obstacles of all informants stated that there was a tendency for the economic factor of a student which made students have to earn income and undergo lectures, and busy factors in the organization made students complacent to work on their final project. Keywords: Students, Final Project